Investasi Saham dalam Islam : Landasan Syariah dan Praktik - Wanda Fatoni Putri; Dzulfani Nur Hidayanti; Maliq Muzhafran; Ismail Fauzan Ramadhan (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
Stocks are one of the most popular investment instruments due to their high profit potential. However, in the Islamic view, stock investment requires special consideration to ensure its compliance with sharia principles. This study aims to explain the concept of stocks in the Islamic perspective, the criteria for halal stocks, and the ethical principles that must be applied in investment activities. In Islam, stocks are considered halal if the company that manages its business does not conflict with sharia, such as avoiding usury, gambling, and businesses that contain haram elements. In addition, the stock transaction mechanism must be free from excessive speculation (gharar) and market manipulation. By understanding these principles, Muslim investors can invest responsibly in accordance with Islamic values. This study is expected to provide practical guidance for the public in managing sharia-based investment portfolios.